Revealing atomic-scale vacancy-solute interaction in nickel. (October 2021) - Morgado, Felipe F.; Katnagallu, Shyam; Freysoldt, Christoph; Klaes, Benjamin; Vurpillot, François; Neugebauer, Jörg; Raabe, Dierk; Neumeier, Steffen; Gault, Baptiste; Stephenson, Leigh T.
Abstract: It is widely accepted that the different types of crystalline imperfections, such as vacancies or dislocations, greatly influence a material's physical and mechanical properties. However, imaging individual vacancies in solids and revealing their atomic neighborhood remains one of the frontiers of microscopy and microanalysis. Here, we study a creep-deformed binary Ni-2 at.% Ta alloy. Atom probe tomography reveals a random distribution of Ta. Field ion microscopy, with contrast interpretation supported by density-functional theory and time-of-flight mass spectrometry, evidences a positive correlation of Ta with vacancies, supporting positive solute-vacancy interactions previously predicted by atomistic simulations. Graphical abstract: Image, graphical abstract